Potensi Lazisnu dalam Meningkatkan Sosial Ekonomi Masyarakat Kota Sorong Papua Barat - Hamzah Hamzah; St Umrah (Khazanah Theologia, 2019)
One of the worship in Islam is the implementation of zakat, infaq and Shadaqah (ZIS). On the other hand, ZIS is also an effective solution in empowering the social economy. This study aims to elaborate the potential and socio-economic assistance of the community conducted by LAZISNU Sorong. The research method uses descriptive qualitative research with NU leaders, LAZISNU Sorong managers and beneficiary communities as informants in the study. Data collected by observation, interview and documentation. The Miles and Huberman model analysis technique is used as an analysis tool. The results of this study show that the number of Nahdiyin (member of Nahdlatul ulama) residents and a solid and competent management team is a potential in the development of LAZIZNU. There are 4 models of excellent programs that continue to be carried out, including: NUSmart, NUPrenuer, NUSkill, and NUCare as pillars of improving the social economy of the community. In addition, the activation of the District Level NU Deputy Council, and the establishment of new branches and UPZIS can reach muzaqqi and munfiq in the interior into an effort in institutional optimization.